2016
DOI: 10.1088/0741-3335/58/4/045025
|View full text |Cite
|
Sign up to set email alerts
|

Combined proton acceleration from foil targets by ultraintense short laser pulses

Abstract: Proton emission from solid foil targets irradiated by relativistically intense femtosecond laser pulses is studied experimentally. Broad plateaus in energy spectra are measured from micron-thick targets when the incident laser pulses have relatively low intensity contrasts. It is proposed that such proton spectra can be attributed to the combined processes of laserdriven collisionless shock acceleration and target normal sheath acceleration. Simple analytic estimation and two-dimensional particle-in-cell simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…The system parameters of that investigation are not widely dissimilar to the ones in Ref. [31]. It was con- firmed that the number density of CSA protons is small compared to TNSA, even under ideal conditions 3 .…”
Section: Effects Of Target Thicknessmentioning
confidence: 66%
See 1 more Smart Citation
“…The system parameters of that investigation are not widely dissimilar to the ones in Ref. [31]. It was con- firmed that the number density of CSA protons is small compared to TNSA, even under ideal conditions 3 .…”
Section: Effects Of Target Thicknessmentioning
confidence: 66%
“…Fang et al [31] is, to our knowledge, the first investigation to focus solely on this plateau phenomenon, where the existence of an energy plateau is dependent on the laser intensity contrast. It was found that the higher the contrasts became, the shorter the plateau region, inferring a complex proton generation mechanism at relatively low contrast (10 8 ) and strongly suggesting that pre-plasma plays a major part in this mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The repetition rate of the laser system is 10 Hz, however, the experiment discussed here, was conducted at 0.2 Hz. In addition to compatible with the target system, this allows sufficient time for effective cooling of the lasing materials, which leads to the stability of the laser beam parameters and focusability [27]. The amplified spontaneous emission contrast (ASE) to the main peak was measured to be 10 −8 at 10 ps by a scanning third-order auto correlator [27].…”
Section: Methodsmentioning
confidence: 99%
“…The contrast of the amplified spontaneous emission (ASE) to the main peak was measured to be 10 -8 at 10 ps using a scanning third-order autocorrelator (Sequoia). 19 Fig. 1 shows a schematic of the experimental setup.…”
Section: Introductionmentioning
confidence: 99%